Challenges and strategies in conducting sexual and reproductive health research among Rohingya refugees in Cox’s Bazar, Bangladesh - Ahmed, Rushdia; Aktar, Bachera; Farnaz, Nadia; Ray, Pushpita; Awal, Abdul; Hassan, Raafat; Bin Shafique, Sharid; Hasan, Md Tanvir; Quayyum, Zahidul; Jafarovna, Mohira Babaeva; Kobeissi, Loulou Hassan; El Tahir, Khalid; et al. (BMC, 2022)
This article was published in Conflict and Health by BMC [© The Author(s). 2020, corrected publication 2020. Open Access This article is licensed under a Creative Commons Attribution 4.0 International License,] and the definite version is available at: https://doi.org/10.1186/s13031-020-00329-2 The Journal's website is at: https://conflictandhealth.biomedcentral.com/articles/10.1186/s13031-020-00329-2